The Role of Platelet-Rich Fibrin (PRF) Membrane in Regulating Interleukin (IL)-1 and Vascular Endothelial Growth Factor (VEGF) Expression in Strabismus Surgery - Dinar Rahmaniah, Amanda; Indriaswati, Luki; Prastyani, Reni (Journal of Neonatal Surgery, 2025)
Strabismus surgery is a common procedure for correcting ocular misalignment. However, a major challenge in achieving optimal surgical outcomes is the risk of excessive postoperative inflammation, which can lead to fibrosis. This inflammatory response is primarily driven by the release of pro-inflammatory cytokines such as Interleukin (IL)-1 and pro-angiogenic factors like Vascular Endothelial Growth Factor (VEGF). While these mediators are essential for wound healing by promoting fibroblast activity, angiogenesis, and vascular permeability, their uncontrolled expression may result in excessive fibrosis, ultimately impairing ocular motility. A promising solution is the use of Platelet-Rich Fibrin (PRF) membrane, a second-generation platelet concentrate with both anti-inflammatory and regenerative properties. A review of existing literature highlights PRF’s potential in enhancing wound healing. Despite its well-documented benefits in various surgical fields, its application in ophthalmic procedures, including strabismus surgery, remains underexplored. Given these promising findings, further research on PRF’s role in strabismus surgery is warranted. This study aims to investigate the effect of PRF on IL-1 and VEGF expression, offering insights into its potential as an alternative strategy for improving surgical outcomes. PRF is expected to be a promising approach for reducing inflammation, preventing excessive fibrosis, and minimizing postoperative complications in strabismus surgery. However, further experimental and clinical studies are needed to validate its effectiveness.